2018 IEEE 5th International Congress on Information Science and Technology (CiSt) 2018
DOI: 10.1109/cist.2018.8596653
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Management to Support Learning Analytics in Higher Eduction

Abstract: This paper argues based on evidence from the literature that learning analytics, when undertaken by higher education institutions, is not considered within a holistic knowledge management strategy, which could provide significant improvement to the outcomes of learning analytics. Particularly, a synthesis of knowledge extraction via learning analytics and appropriate handling of such knowledge via knowledge management is not typically implemented in higher education practices, but it constitutes a promising pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…One of the KM tools that facilitates e-learning is the LMS (Alenezi et al, 2018;Al-Jedaiah, 2020;Hantoobi et al, 2021;Min et al, 2012;Okfalisa et al, 2020). LMS integration into teaching and learning activities plays a crucial role in knowledge production because it improves the process of obtaining knowledge and information, disseminating knowledge in the platform and learning activities, and assessing student knowledge.…”
Section: Knowledge Management Learning and Learner Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the KM tools that facilitates e-learning is the LMS (Alenezi et al, 2018;Al-Jedaiah, 2020;Hantoobi et al, 2021;Min et al, 2012;Okfalisa et al, 2020). LMS integration into teaching and learning activities plays a crucial role in knowledge production because it improves the process of obtaining knowledge and information, disseminating knowledge in the platform and learning activities, and assessing student knowledge.…”
Section: Knowledge Management Learning and Learner Outcomesmentioning
confidence: 99%
“…Understanding the efficiency of employing an LMS to inculcate knowledge (input and output of the educational process) in students is critical for Malaysian higher education institutions. Recent LMS-evaluation research has identified the need to analyze the implementation of knowledge management (KM) in respective institutions' platform systems to ease the learning process, especially by expanding it across several knowledge areas (Alenezi et al, 2018;Al-Jedaiah, 2020;Hantoobi et al, 2021;Okfalisa et al, 2020). LMSs use KM to create, share, apply, and process information into implicit knowledge that can transform students' thinking and enrich their experience.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within a classroom, they are an effective tool to track the evolution and performance of a large cohort of students (De Meester, Lieber, Dimou, & Verborgh, 2018). At a school management level, they can be applied to understand larger trends in performance, while at a regional or national level, it can be applied to drive educational policies (Alenezi, Emmanouilidis, & Al-Ashaab, 2018;Tsai et al, 2018).…”
Section: Introductionmentioning
confidence: 99%